Genomes of two new ammonia-oxidizing archaea enriched from deep marine sediments. - Soo-Je Park; Rohit Ghai; Ana-Belén Martín-Cuadrado; Francisco Rodríguez-Valera; Won-Hyong Chung; KaeKyoung Kwon; Jung-Hyun Lee; Eugene L Madsen; Sung-Keun Rhee (PLoS ONE)
Ammonia-oxidizing archaea (AOA) are ubiquitous and abundant and contribute significantly to the carbon and nitrogen cycles in the ocean. In this study, we assembled AOA draft genomes from two deep marine sediments from Donghae, South Korea, and Svalbard, Arctic region, by sequencing the enriched metagenomes. Three major microorganism clusters belonging to Thaumarchaeota, Epsilonproteobacteria, and Gammaproteobacteria were deduced from their 16S rRNA genes, GC contents, and oligonucleotide frequencies. Three archaeal genomes were identified, two of which were distinct and were designated Ca. "Nitrosopumilus koreensis" AR1 and "Nitrosopumilus sediminis" AR2. AR1 and AR2 exhibited average nucleotide identities of 85.2% and 79.5% to N. maritimus, respectively. The AR1 and AR2 genomes contained genes pertaining to energy metabolism and carbon fixation as conserved in other AOA, but, conversely, had fewer heme-containing proteins and more copper-containing proteins than other AOA. Most of the distinctive AR1 and AR2 genes were located in genomic islands (GIs) that were not present in other AOA genomes or in a reference water-column metagenome from the Sargasso Sea. A putative gene cluster involved in urea utilization was found in the AR2 genome, but not the AR1 genome, suggesting niche specialization in marine AOA. Co-cultured bacterial genome analysis suggested that bacterial sulfur and nitrogen metabolism could be involved in interactions with AOA. Our results provide fundamental information concerning the metabolic potential of deep marine sedimentary AOA.